Uday Shankar and the Dartington Hall Trust: patronage, imperialism and the Indian dean of dance. Issue 3 (3rd July 2018) - Vertinsky, Patricia; Ramachandran, Aishwarya
ABSTRACT: When George Bernard Shaw called Dartington Hall 'a Salon in the Countryside', it was a paean to its wealthy owners and their 'utopian' plans to establish a place of experiment and innovation in the Devonshire countryside in the 1920s. The Elmhirsts prioritised dance from the beginning, lavishing considerable resources upon its development, such that when Oriental dancer Uday Shankar was introduced to Dartington in 1934 he found willing benefactors to support his desired centre for dance in India. Artists are seldom born with silver spoons in their mouths, but even if so fortunate, they sometimes take pleasure in inviting troubles throughout their lives. Shankar's dance centre foundered within four years, mired in his financial mismanagement and artistic disagreements in the face of wide-ranging political turmoil in India. This article explores how the motives of Uday Shankar's patrons, at a time of heightened anti-colonial sentiment in India and a rapidly changing cultural and artistic landscape, ranged from artistic to educational, from political to personal. And while his patrons long sustained Shankar, their support was ultimately contingent on their view of the educational potential of his work rather than his desire to forge a renaissance in Indian dance culture.